Using Terms and Conditions to apply Fundamental Rights to Content Moderation - Quintais, João Pedro; Appelman, Naomi; Ó Fathaigh, Ronan (German law journal, 2023)
Large online platforms provide an unprecedented means for exercising freedom of expression online and wield enormous power over public participation in the online democratic space. However, it is increasingly clear that their systems, where (automated) content moderation decisions are taken based on a platformʼs terms and conditions (T&Cs), are fundamentally broken. Content moderation systems have been said to undermine freedom of expression, especially where important public interest speech ends up suppressed, such as speech by minority and marginalized groups. Indeed, these content moderation systems have been criticized for their overly vague rules of operation, inconsistent enforcement, and an overdependence on automation. Therefore, in order to better protect freedom of expression online, international human rights bodies and civil society organizations have argued that platforms “should incorporate directly” principles of fundamental rights law into their T&Cs. Under EU law, and apart from a rule in the Terrorist Content Regulation, platforms had until recently no explicit obligation to incorporate fundamental rights into their T&Cs. However, an important provision in the Digital Services Act (DSA) will change this. Crucially, Article 14 DSA lays down new rules on how platforms can enforce their T&Cs, including that platforms must have “due regard” to the “fundamental rights” of users under the EU Charter of Fundamental Rights. In this article, we critically examine the topic of enforceability of fundamental rights via T&Cs through the prism of Article 14 DSA. We ask whether this provision requires platforms to apply EU fundamental rights law and to what extent this may curb the power of Big Tech over online speech. We conclude that Article 14 will make it possible, in principle, to establish the indirect horizontal effect of fundamental rights in the relationship between online platforms and their users. But in order for the application and enforcement of T&Cs to take due regard of fundamental rights, Article 14 must be operationalized within the framework of the international and European fundamental rights standards. If this is possible Article 14 may fulfil its revolutionary potential.